Chemical and physical characteristic of nano charcoal ash from coconut shell in bitumen as alternative binder - Putra Jaya, Ramadhansyah; Siti Nur Amiera, Jeffry; Norhidayah, Abdul Hassan; Haryati, Yaacob; Ekarizan, Shaffie; Kamil, Arshad (Universiti Malaysia Perlis, 2020)
Good quality of pavement should have high structural integrity, which provides a strong, smooth, and safe riding surface for road users. In Malaysia, a common type of distress in asphalt pavement is permanent deformation. This study attempts to investigating NCA from coconut shell that is utilized as the main material in the bitumen modification. The effects of NCA on the bitumen subjected to numerous grinding times are evaluated, and the optimum grinding time that can produce the optimum NCA is determined. The optimum grinding time that showed the highest performance of bitumen was 30 h, which produced the optimum size of 148 nm. The incorporation of NCA increased the stiffness of the bitumen up to 47% and increased the softening point value by approximately 12% higher than the virgin binder. The PI values for the modified bitumen were not within the specified range, but the values did not exceed −2, except for the NCA0 and NCA5.